The weekday/weekend ozone differences induced by the emissions change during summer and autumn in Guangzhou, China. (15th February 2019) - Zou, Y.; Charlesworth, E.; Yin, C.Q.; Yan, X.L.; Deng, X.J.; Li, F.
Abstract: Weekday/weekend mixing ratios of ozone (O3 ) and the O3 precursors of non-methane hydrocarbons (NMHCs) and nitrogen oxides (NO x ) were recorded at the Guangzhou Panyu Atmospheric Composition Station (GPACS), a suburban site in Guangzhou, during the summer (June, July, and August) and autumn (September, October, and November) of 2011. In both summer and autumn, weekday/weekend O3 differences in the morning and at midday largely depend on how much the O3 precursors are affected by anthropogenic emissions. In the mornings (6:00–9:00 LT), pollutants (i.e. NO x and NMHCs) were more strongly influenced by vehicular emissions in autumn than in summer. In autumn, O3 titration and lower NO x on weekends in NMHCs-limited regimes lead to more rapid O3 production, which resulted in the O3 weekend effect during autumn morning. No O3 weekend effect occurred on summer mornings because O3 formation was in a NO x -limited regime, although O3 titration still existed. At midday (10:00–16:00 LT), the increase of biogenic NMHCs emissions reversed the sensitivity of O3 production from NMHCs-to NO x -sensitive. The weekday/weekend diurnal pattern of vehicular sources was the same at midday, more intense other human industrial activities in autumn not only gave rise to the higher mixing ratios of high-reactive anthropogenic NMHCs (e.g. aromatics) on weekdays, but also could affected the temperature in the city, leading to higher isoprene mixing ratio on weekdays. All these factors are likely to contribute to the O3 weekday effect in autumn. Meanwhile no weekday O3 effect occurred in summer due to the low-intensity industrial anthropogenic activities. Our results show that high-reactive NMHCs and NO x control can be effective for reducing peak O3 mixing ratios in Guangzhou. Further investigation based on numerical models is required to reach more robust conclusions. Highlights: Presence of O3 weekend effect in the morning depends on how much the O3 precursors are affected by vehicular emissions. The increase of biogenic NMHCs emissions at midday reverses the O3 production from NMHCs-sensitive to NO x -sensitive. Presence of O3 weekday effect at midday bases on how much the high-reactive NMHCs are affected by industrial emissions.